Seasonal Variation of Yields and Nutrient Uptakes of IR-64 Grown in Terraced Paddy Field System - yonubowo, Sukristi; Laing, Gijs Du (JOURNAL OF TROPICAL SOILS, 2011)
In the past, most rice study was carried out in irrigated lowland rice and less or no attention was paid to the terraced paddy field system. Study on seasonal rice biomass production and nutrient uptake variation of IR-64 variety cultivated in terraced paddy field system was carried out in Keji Village, Ungaran Sub district during the wet season 2003-04 and dry season 2004. The aim of the study was to evaluate the seasonal variation of rice biomass productions, nutrient concentrations and nutrient uptakes of IR-64. Data were taken from four treatments, namely conventional farmer practice, conventional farmer practices + rice straw, improved technology and improved technology + rice straw. For the conventional farmer practice, only 50 kg of urea ha-1 season-1 was applied. Meanwhile, about 100 kg each of urea, triple super phosphate, and potassium cloride ha-1 season-1 were applied in the improved technology treatments. About 33% of rice straw produced from the previous season was recycled in the treatments of conventional farmer practices + rice straw and improved technology + rice straw. Each treatment was replicated three times and arranged in a Randomised Completely Block Design. Plants were sampled five times, at 45, 60, 75, 90 and 105 days after transplanting. The results indicated that overall production of the improved technology + rice straw treatment was significantly higher than the other treatments both in the wet season 2003-04 and the dry season 2004. Rice grains and rice residues in the dry season were higher than in the wet season, except for the rice straw. However, statistically, there were no significant variations of rice biomass production between the wet season 2003-04 and the dry season 2004. When the rice straw addition was considered, only rice grain production of the dry season was consistently greater than the rice grain production of the wet season. Concentrations of N, P, and K in shoots and roots significantly decreased during rice growth. In contrast to the concentrations, the nutrient uptake increased by the time of rice growth. The highest nutrient concentrations both in the wet and dry season were observed at 45 days after. Contrary to the nutrient concentrations, the highest N, P, and K uptakes were taken place at harvest.Â  Seasonally, nutrient uptakes at harvest in the dry season were higher than in the wet season, but statistical evidences were not consistent. As only rice residues were left in the field, the nutrient amounts taken up by rice straw and rice grains reflect the nutrients removal from the field through harvest. The total nutrients removal ranged between 114 and 119 kg N, 10 and 12 kg P, 133 and 148 kg K ha-1 season-1.